1999
DOI: 10.1126/science.283.5399.217
|View full text |Cite
|
Sign up to set email alerts
|

Female × Male Interactions in Drosophila Sperm Competition

Abstract: In several organisms, the success of a male's sperm in multiply inseminated females depends on the male's genotype. In Drosophila, the female also plays a role in determining which sperm are successful. Pairwise tests among six isogenic lines of Drosophila melanogaster were performed to determine whether there is a genotype-specific interaction in the success of sperm. The success of a particular male's sperm was found to depend on the genotype of the female with which he mates, providing evidence for an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
355
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(385 citation statements)
references
References 24 publications
25
355
1
Order By: Relevance
“…First, we show that there are measurable fitness benefits associated with these chemically moderated gamete preferences; sperm preferentially swim towards eggs that not only deliver higher fertilization rewards (this study and [22]) but also those that yield higher post-zygotic survival rates. In other contexts, previous studies have reported significant male-by-female interactions at fertilization [33,34], but the question of whether 'compatible' combinations of sperm and eggs yield high post-zygotic survival has received less attention, and some studies investigating this topic in other contexts have reported no significant association between fertilization and offspring viability [23 -25]. Our study provides evidence that in M. galloprovincialis, the fertilization benefits of sperm chemoattraction extend 'upstream' to include enhanced offspring viability.…”
Section: Discussionmentioning
confidence: 99%
“…First, we show that there are measurable fitness benefits associated with these chemically moderated gamete preferences; sperm preferentially swim towards eggs that not only deliver higher fertilization rewards (this study and [22]) but also those that yield higher post-zygotic survival rates. In other contexts, previous studies have reported significant male-by-female interactions at fertilization [33,34], but the question of whether 'compatible' combinations of sperm and eggs yield high post-zygotic survival has received less attention, and some studies investigating this topic in other contexts have reported no significant association between fertilization and offspring viability [23 -25]. Our study provides evidence that in M. galloprovincialis, the fertilization benefits of sperm chemoattraction extend 'upstream' to include enhanced offspring viability.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not the sperm competitive superiority of the B2 haplogroup is intrinsic or dependent on female haplogroup remains to be determined, since only A-haplogroup females were used in this experiment. Given the evidence of male and female genotype effects on sperm competition in other species [44,45], it is possible that sperm competitive ability in C. scorpioides may be influenced by female mitochondrial haplogroup. While haplogroup-dependent cryptic female choice favouring B2 sperm could theoretically account for the B2 male advantage in fertilization, this hypothesis is not consistent with the results of our assessment of possible haplotype effects on female reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying the evidence for sexual selection on ejaculates is corresponding evidence that selection can favour female reproductive traits that serve to bias fertilizations towards either 'preferred' [5] or genetically compatible mates [6][7][8]. Sperm competition can therefore be underpinned by effects attributable to both sexes, including relative differences in the sperm competitive ability of rival males [9][10][11], consistent biases in fertilization rates that are mediated by female effects [12], and complex interactions involving the genotypes of competing males and females [13][14][15]. Consequently, disentangling these processes, and in particular the relative importance of males, females and their interacting effects in sperm competition, poses a significant empirical challenge [16,17].…”
Section: Introductionmentioning
confidence: 99%